Interactive Module Development of Teacher's Measurements - Mohd Razimi Husin; Ismail Yusuf Panessai; Hishamuddin Ahmad (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2018)
This research develops an interactive module system that can be used to explore and build a self-assessment checklist on significant learning content in the daily life and work of students in the future. The purpose of this interactive module system is to contribute to the teacher in choosing the appropriate learning content for teaching. This study will focus on the contents of Form 1 history subjects involving teachers and students. In addition, with a self-assessment checklist of teachers, educators can use it in determining significant learning content with the life and nature of student work. The built-in interactive module system also benefits pupils when the learning takes place content and skills that can be used all the time. The data were obtained through field observations in the classroom and teacher work. In general, the use of interactive module systems developed is very good and effective. The findings show that the majority of users have stated that the developed system interface is of interest to the user, in which the navigation system developed is user-friendly. The user states that the usability of the developed system is very helpful to teachers and students in understanding the content of the given lessons.